Land degradation, flood disaster, and local wisdom in Tempe Lake of South Sulawesi coastal community - Harifuddin, Harifuddin; Azuz, Faidah; Madiong, Baso (Brawijaya University, 2025)
Floods that hit the coast of Lake Tempe are caused by land degradation and poor land management. This research aims to analyse (1) land degradation as a determinant factor in the occurrence of flood disasters, (2) the function of local wisdom as an adaptation to flooding, (3) the effects of land degradation on the sustainability of the fishermen’s livelihoods of coastal communities. This research used an exploratory-consequential (qualitative-quantitative) design. This research was conducted on the coast of Tempe Lake, utilizing data collection methods that included interviews, observations, literature studies, questionnaires, and documentation. Data analysis used 3-step technique (qualitative) and descriptive statistics (quantitative). The results showed that (1) almost all respondents stated that land degradation such as sedimentation and land erosion that lasted for a long time and the amount of critical land due to wrong land management triggered flooding. (2) In reading natural signs, local wisdom serves as an early warning so that people are aware of the disasters that will occur, (3) the professions most affected by flooding are farmers, fishermen, and transport boat drivers. When flooding occurs farmers and fishermen cannot work but they can become transport boat drivers. For the transport boat driver, his boat can be rented out when he isn’t working. The conclusion is that land degradation causes floods. However, the experience of flooding over the years has made people adapt, including in terms of work, so that they still have alternative productive activities despite being hit by floods.